A Technique to Infer Magnetic Topology at Mars and Its Application to the Terminator Region. Issue 3 (28th March 2019) - Xu, Shaosui; Weber, Tristan; Mitchell, David L.; Brain, David A.; Mazelle, Christian; DiBraccio, Gina A.; Espley, Jared
Abstract: Magnetic topology is important for understanding the Martian plasma environment, including particle precipitation, energy transport, cold ion escape, and wave‐particle interaction. In this study, we combine two independent but complementary methods in order to determine magnetic topology based on superthermal electron energy and pitch angle distributions. This approach removes ambiguities that result from using either energy or pitch angle alone, providing a more accurate and comprehensive determination of magnetic topology than previous studies. By applying this combined technique, we are able to identify seven magnetic topologies, including four types of closed field lines, two types of open field lines, and draped. All seven topologies are present in the Mars environment and are mapped in longitude, latitude, solar zenith angle, and altitude with the combined technique near the terminator. We find that closed field lines with double‐sided loss cones are frequently present over stronger crustal field regions at higher altitudes. We also show that the cross‐terminator closed field lines are more spatially confined over strong crustal regions, likely connecting nearby magnetic crustal patches. In contrast, cross‐terminator closed loops over weak crustal regions have more distantly separated foot points, most likely connecting distant crustal patches. Key Points: A technique combining e‐ pitch angle and energy distribution is developed to most accurately infer up to seven magnetic topologies at Mars Closed magnetic loops with trapped electrons occur frequently over stronger crustal field regions at higher altitudes Cross‐terminator closed loops are more spatially confined over strong crustal regions and distantly separated over weak crustal regions